Dissecting perceptions of new graduates on work orientation and self-confidence in employability skills training program - Mohd Puad, Mohd Hazwan; Mohamad Desa, Hazeem (Horizon Research Publishing, 2020)
Work orientation and self-confidence are among key factors that lead to work performance of individual. Both factors are considered as among the predictors to influence productivity of new and experienced workers. This study is aimed to identify the level of work orientation and self-confidence among new graduates who participated in the work retention and skills enhancement program, Skim Latihan 1 Malaysia (SL1M). Also the study is intended to assess trainees’ perceptions on employability skills training program, SL1M. This is a quantitative study using descriptive design. A total of 108 respondents were randomly selected from new graduates who were involved in the SL1M training program. This study is a quantitative research by using questionnaire instrument. Descriptive data were analyzed by using IBM SPSS Statistics software. The findings indicate the level of work orientation and self-confidence was high among respondents. The SL1M trainees are prepared to change their method of work if necessary in order to fulfill work requirement and demand. The trainees also believe that they possess a quality to work in the industry and can be offered to employers.